Monitoring Forced Labour and Slavery in Global Supply Chains: The Case of the California Act on Transparency in Supply Chains. Issue 4 (29th November 2017) - Koekkoek, Marieke; Marx, Axel; Wouters, Jan
Abstract: Supply chains have more and more become global supply chains, due to which it becomes increasingly more difficult for states to monitor whether the production process of goods entering the territory has been free of labour rights abuses. States are less able to hold corporate entities accountable that are knowingly or unknowingly benefiting from labour rights abuses. Transparency measures have been suggested as a way to close this accountability gap and circumvent traditional issues of enforcement when production and consumption of goods takes place in different jurisdictions. This paper discusses whether transparency measures live up to these expectations by assessing the California Transparency in Supply Chains Act (California Act). We analyse whether the Act does indeed contribute to greater accountability by filling the existing information gap between companies and consumers. The workings of the Act, as well as its impact on primary stakeholders will be determined. The paper discusses action taken by companies, consumers and non‐governmental organizations by looking at the degree to which the new California Act generated differences in behaviour and practices of these affected parties. Based on this information the question is answered which possibilities and limitations are connected to the use of transparency measures in combatting the abuse of labour rights in the global supply chain. It is discussed which lessons can be learned from the California Act and which policy implications this could have for future transparency measures. Abstract : Transparency measures have a potential of better informing consumers and increase accountability of companies with respect to their supply chain.